An Exemplary Doctor and Idealist Scientist: Prof. Ekrem Kadri Unat - Ada, Turhan (DOC DESIGN INFORMATICS CO LTD, 2024)
Prof. Dr. Ekrem Kadri Unat (1914-1998) graduated from & Idot;stanbul University Faculty of Medicine in 1937 and was appointed resident at the Institute of Microbiology. He received the title of bacteriologist in 1940. In 1942, he became an associate professor of microbiology with his thesis The Strength of Embryonated Ascarid Eggs. In 1946, he went to the USA, working with Prof. Dr. Fred D. Weidman at the Department of Dermatology, Faculty of Medicine, University of Pennsylvania. He completed his residency in the Department of Public Health at Johns Hopkins University in 1948. In 1949, he returned to T & uuml;rkiye and started working at the Institute of Microbiology at & Idot;stanbul University. In 1951, he founded the World Health Organization Tuberculosis Laboratory. In 1958, he became a professor and the director of the Institute of Parasitology, which he founded. He published 35 books, ten monographs, 15 meeting books, ten congress reports and 360 articles.
Keywords: Ekrem Kadri Unat; medicine; microbiology; General & Internal Medicine